The Effect of Combination of Classical Music Therapy and Progressive Muscle Relaxation on Stress Score of Final Project of D-III Nursing Students at Bakti Tunas Husada University - Arsilia Fitriawati, Devita; Cahyati, Peni; Kustiawan, Ridwan; Riyana, Asep (Media Informasi, 2025)
Final year students often experience stress in the process of preparing their final project which can interfere with mental health and reduce academic quality. Stress is an individual's inability to deal with challenges that are being faced by someone. This condition can be triggered by various things, such as physical pressure, social situations and even uncontrolled environments that can ultimately have an impact on one's own condition. Management of this stress can be done non-pharmacologically which does not involve drugs, but uses other methods such as by performing a combination of classical music therapy and progressive muscle relaxation. Objective: to determine the effect of a combination of classical music therapy and progressive muscle relaxation on the stress score of D-III Nursing students at Bakti Tunas Husada University. The theoretical basis underlying this research is stress, students and classical music therapy and progressive muscle relaxation. Method: using pre experiment with one-group pretest- posttest design on 50 final year students. Sampling using Probability Sampling with Simple Random Sampling. Data were analyzed using the Dependent T test. Results: showed that there was a significant decrease before and after the intervention with an average difference in stress scores of 8.96 with a p-value of 0.000 which means Ha is accepted and Ho is rejected. Conclusion: There is an effect of the combination of classical music therapy and progressive muscle relaxation in reducing stress scores.